Applying Brain Computer Interface Technology for Playing Games - Ankit Mehta; Adarsh Singh; Anshu Kumar; Ankit Katewa; Dr. N K Bansode (International Journal of Engineering and Management Research, 2021)
Brain Computer Interfaces are specialized systems that allows users to control computer applications using their brain waves. Initially, BCI were mostly used in medical field. But after some research and thanks to consumer-grade electroencephalography (EEG) devices, many applications and research opportunities were opened outside of the medical field. One particular area that is gaining more evidence due to the arrival consumer-grade devices is that of computer games, as it allows more user-friendly applications of BCI technology for the general public. In this report, we are going to talk about one of those games, Maze game. It will be a 2D maze, path known to the user. Using the EEG device named Neurosky Brain Wave Kit user will be able to move the avatar in order to reach the goal from the starting position.